Relationship key factor of inflammation and the development of complications in the late period of myocardial infarction in patients with visceral obesity. Issue 1 (December 2017) - Gruzdeva, Olga; Uchasova, Evgenya; Dyleva, Yulia; Akbasheva, Olga; Matveeva, Vera; Karetnikova, Victoria; Kokov, Alexander; Barbarash, Olga
Abstract Background Cytokines play an significant role in regulating non-specific inflammatory response involved in many pathological processes. The current study tested the hypothesis that myocardial infarction in patients with obesity can lead to increased production of proinflammatory cytokines and unfavorable course of the pathological process. Methods The study recruited 232 male patients with ST-elevated myocardial infarction. The mean age of the patients was 58.7 (52.2-69.9) years. All the patients were assigned to two groups according to the computed tomography findings: 1 (n = 160) patients with visceral obesity (VO), and 2 (n = 72) patients without VO. Interleukins were measured in blood serum on days 1 and 12 after MI. Results All patients with MI demonstrated elevated levels of proinflammatory markers and reduced anti-inflammatory markers in the in-hospital period. The results suggested that among all studied inflammatory markers IL-6 (OR 1.9; 95% CI (1.6–2.8) and CRP (OR 1.3; 95% CI (1.1–1.8) were closely related to VO. One year after MI adverse cardiovascular outcome frequently occurred in patients with VO. There were two cardiac deaths (3.1%), 6 cases (9.3%) of recurrent MI, 19 cases (29.6%) of repeated hospitalizations for unstable angina, whereas only 2 patients without VO (6.6%) were hospitalized for unstable angina. The results of the logistic regression analysis demonstrated that IL-6, IL-12, and IL-10 had the highest predictive value for occurrence of adverse cardiovascular events in patients with VO. Conclusion Cytokine profile in MI patients with VO is characterized by an imbalance caused by elevated pro-inflammatory interleukins and decreased anti-inflammatory interleukins. Obesity in patients was associated with a marked increase in IL-6 and CRP levels.